Szanse i zagrożenia dla sektora banków komercyjnych w Polsce oraz perspektywy jego rozwoju. Część 1 - Swacha-Lech, Magdalena (Threats and Opportunities for the Bank Sector in Poland and its Development Perspectives. Part I, 2005)
The aim of the article is to identify the most important tendencies which boost the development of the commercial banks sector in Poland as well as the phenomena that can disturb its functioning. The process is based on the analysis of the following elements of bank environment: legal, social- economic, competitive and technological. The conducted analysis is the opening point for defining successful directions for the development of the commercial banks, which will constitute the second part of this work.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 119-130